Real-world clopidogrel utilization in acute coronary syndromes: patients selection and outcomes in a single-center experience. (December 2017) - Castini, Diego; Persampieri, Simone; Cazzaniga, Sara; Ferrante, Giulia; Centola, Marco; Lucreziotti, Stefano; Salerno-Uriarte, Diego; Sponzilli, Carlo; Carugo, Stefano
Background: With this study, we sought to identify patient characteristics associated with clopidogrel prescription and its relationship with in-hospital adverse events in an unselected cohort of ACSs patients. Materials and Methods: We studied all consecutive patients admitted at our institution for ACSs from 2012 to 2014. Patients were divided into two groups based on clopidogrel or novel P2Y12 inhibitors (prasugrel or ticagrelor) prescription and the relationship between clopidogrel use and patient clinical characteristics and in-hospital adverse events was evaluated using logistic regression analysis. Results: The population median age was 68 years (57–77 year) and clopidogrel was prescribed in 230 patients (46%). Patients characteristics associated with clopidogrel prescription were older age, female sex, non-ST-elevation ACS diagnosis, the presence of diabetes mellitus and anemia, worse renal and left ventricular functions and a higher Killip class. Patients on clopidogrel demonstrated a significantly higher incidence of in-hospital mortality (4.8%) than prasugrel and ticagrelor-treated patients (0.4%), while a nonstatistically significant trend emerged considering bleeding events. However, on multivariable logistic regression analysis female sex, the presence of anemia and Killip class were the only variables independently associated with in-hospital death. Conclusion: Patients treated with clopidogrel showed a higher in-hospital mortality. However, clinical variables associated with its use identify a population at high risk for adverse events and this seems to play a major role for the higher in-hospital mortality observed in clopidogrel-treated patients.